CONSUMPTION OF ONLINE POLITICAL NEWS AND POLITICAL PARTICIPATION OF FIRST-TIME VOTERS - Effendi, Ridwan; Haryanegara, Muhammad Endriski Agraenzopati; Sukmayadi, Vidi; Aziz, Firman (JURNAL PENDIDIKAN ILMU SOSIAL, 2020)
In some countries, it is stated that youth political participation tends to decline, and the media are then regarded as ones of the causes of this decline. This is strongly supported by the media perspective. However, it is undeniable that there are contradictions to these views, which bring forth the mobilization perspective. There are also parties who consider that the media have merits in increasing political participation. In this case, communication plays an important role as an analytical tool to determine the effect of online political news consumption on political participation. Political knowledge is used as a mediator in this study. This study was conducted to see the position of Consumption of Online Political News in influencing Political Participation through Political Knowledge among Students. The study employed a quantitative method through questionnaires as an effort to collect and analyze data through regression analysis. Population in this study is Universitas Pendidikan Indonesia’s student that used online news portal. The questionnaires were distributed to 100 student respondents. Sampling method of this study using purposive sampling with several criterias. The results of the study show that there is a significant effect of online political news consumption on political participation with a direct value 0,719.